Le mouvement protestataire algérien de 2019 à la lumière de la théorie des mouvements sociaux et des Printemps arabes - Frédéric Volpi (L’Année du Maghreb, 2019)
How exceptional is the 2019 social unrest in Algeria? If it is exceptional what are its characteristics? Alternatively, is this wave of discontent merely a variation of the movements of the 2011 Arab Uprisings? Social movement theory proposes different frameworks to make sense of these mobilizations and their political outcomes. Although these analytical perspectives were only recently systematically applied to the Middle East and North Africa, their methodological and analytical tools bring some useful insights on events like the current wave of mobilization in Algeria. They help structuring and explaining to varying degrees what constitutes the specificities of the 2019 Algerian movement and what represents generic processes of protest movements. In this light, this contribution seeks to reposition this particular movement within the larger field of social movements in order to highlight its likely trajectory as well as its novel character in relation to the reconfiguration of authoritarian governance in the country.